Racismo y educación: cartografías de la investigación reciente - Olmos Alcaraz, Antonia; Serrano Torres, Tamara (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
This paper has as main aim to review the recent academic and scientist production about racism and education. To do that we are made a bibliographical review in DIALNET (with Spanish, Portuguese and Latin-American resources) that has permit us to show the disciplines interested in this questions, the methodologies employed, the persons object of study or intervention, the kind and the levels of education studied, and, finally, the context of production of the researches. The goal is to build a kind of cartography that shows us how is being the he academic and scientists production of these issues nowadays.